Cationic η3-allyl sulfide complexes of nickel(II) for the polymerization of butadiene in aqueous emulsion - Padavattan, Govindaswamy; Jäkel, Christoph; Steinke, Tobias; Reimer, Valentine; Díaz-Valenzuela, Maria Belén; Crewdson, Patrick; Rominger, Frank (Journal of organometallic chemistry, 2010)
Reaction of the dimeric allyl-nickel(II) chloro complex [Ni(η3-C3H5)(μ-Cl)]2 (5) with sulfur donor ligands (L=L10-L13) in the presence of NaBAr4F (Ar4F=3,5-(CF3)2C6H3) gives the corresponding cationic mononuclear complexes of the type [Ni(η3-C3H5)(L)2]+ (1-4) [L=L10=diphenyl sulfide (1); L=L11=4,4′-thiodiphenol (2); L=L12=4,4′-thio-bis(6-tert-butyl-o-cresol) (3); L=L13=4,4′-thio-bis (6-tert-butyl-m-cresol) (4)]. All of these complexes were characterized by elemental analysis and NMR spectroscopy, as well as the representative complex 3 additionally by single-crystal X-ray analysis. In comparison to the known complex [Ni(η3-C3H5)(η6-BHT)][BAr4F] (BHT=3,5-di-tert-butyl-4-hydroxytoluene), the herein described cationic complexes show an increased stability towards water. The activity of the complexes for butadiene polymerization in aqueous emulsions was studied.